High‐Throughput Miniaturized Screening of Nanoparticle Formation via Inkjet Printing. Issue 8 (27th May 2018) - Styliari, Ioanna D.; Conte, Claudia; Pearce, Amanda K.; Hüsler, Amanda; Cavanagh, Robert J.; Limo, Marion J.; Gordhan, Dipak; Nieto‐Orellana, Alejandro; Suksiriworapong, Jiraphong; Couturaud, Benoit; Williams, Phil; Hook, Andrew L.; et al.
Abstract: The self‐assembly of specific polymers into well‐defined nanoparticles (NPs) is of great interest to the pharmaceutical industry as the resultant materials can act as drug delivery vehicles. In this work, a high‐throughput method to screen the ability of polymers to self‐assemble into NPs using a picoliter inkjet printer is presented. By dispensing polymer solutions in dimethyl sulfoxide (DMSO) from the printer into the wells of a 96‐well plate, containing water as an antisolvent, 50 suspensions are screened for nanoparticle formation rapidly using only nanoliters to microliters. A variety of polymer classes are used and in situ characterization of the submicroliter nanosuspensions shows that the particle size distributions match those of nanoparticles made from bulk suspensions. Dispensing organic polymer solutions into well plates via the printer is thus shown to be a reproducible and fast method for screening nanoparticle formation which uses two to three orders of magnitude less material than conventional techniques. Finally, a pilot study for a high‐throughput pipeline of nanoparticle production, physical property characterization, and cytocompatibility demonstrates the feasibility of the printing approach for screening of nanodrug delivery formulations. Nanoparticles are produced in the well plates, characterized for size and evaluated for effects on metabolic activity of lung cancer cells. Abstract : Inkjet printing is employed as a high‐throughput and miniaturized method to screen nanoparticle formulations. Polymer solutions are swiftly dispensed into well plates using two to three orders of magnitude less material than conventional state‐of‐the‐art techniques. Nanoparticle formation, sizes and cytocompatibility are directly assessed in a single well‐plate, minimizing human errors and batch variability, and providing pilot data to assist nanoparticle selection.